2012
DOI: 10.1002/cssc.201290032
|View full text |Cite
|
Sign up to set email alerts
|

Inside Cover: Solvent‐Free Catalytic Depolymerization of Cellulose to Water‐Soluble Oligosaccharides (ChemSusChem 8/2012)

Abstract: Several key factors that govern the catalytic conversion of lignin into smaller molecules have been neglected. In the report by Rinaldi et al. on some of the many different facets of solvents in the hydrogenolysis of diphenyl ether and, ultimately, of organosolv lignin with Raney nickel are uncovered. Most importantly, solvents are not bystanders in these reactions. The Lewis basicity of solvents very much affects the catalytic activity of Raney nickel, so in nonbasic solvents the catalyst is an extremely act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…A rst step in realizing value from these materials is hydrolytic depolymerization to simple sugars. Previous work has shown that cellulose can be readily hydrolyzed by solid acids such as kaolinite 19 and through impregnation with minimal quantities of a strong acid [20][21][22] combined with mechanical processing. Using basic conditions, lignin can also be mechanocatalytically depolymerized.…”
Section: Resultsmentioning
confidence: 99%
“…A rst step in realizing value from these materials is hydrolytic depolymerization to simple sugars. Previous work has shown that cellulose can be readily hydrolyzed by solid acids such as kaolinite 19 and through impregnation with minimal quantities of a strong acid [20][21][22] combined with mechanical processing. Using basic conditions, lignin can also be mechanocatalytically depolymerized.…”
Section: Resultsmentioning
confidence: 99%
“…[1,2] Mechanochemical reactions are usually carried out by milling, grinding, shearing, or pulling reactants in the absence of organic solvents or in the presence of a catalytic amount of them (liquid-assisted grinding, LAG). [3] In organic chemistry many reactions including metal-catalysed transformations, [4,5] organocatalytic [6] and enzymatic processes, [7] lignin [8] and cellulose depolymerizations, [9,10] multicomponent reactions [11] and many other [12,13] have been studied using various ball mill techniques. As a result of these studies, mechanochemical activation and techniques have revealed a variety of benefits, including faster reaction milling times, higher yield, less waste formation, enhanced selectivity, and stoichiometry control, to name a few.…”
Section: Introductionmentioning
confidence: 99%